Multicultural Counselling in the New Millennium: Introduction to the Special Theme Issue - Arthur, Nancy; Stewart, John (Canadian Journal of Counselling and Psychotherapy, 2007)
This article introduces the special theme issue of the Canadian Journal of Counselling on Multicultural Counselling in the New Millennium. First, the cultural diversity of Canadian society is described with an emphasis on changing population demographics in the foreseeable future. Next, perspectives about the multicultural counselling movement are outlined. The discussion then turns to culture-centred counselling competencies in the domains of self-awareness, knowledge, skills, and organizational competencies. Counsellors are invited to consider ways of incorporating culture-centred competencies into their professional practice, future research, and professional development.